Parental Defensiveness about Multifactorial Genomic and Environmental Causes of Children's Obesity Risk - Persky, Susan (Child Obes, 2019)
Background: Future integration of genomics into weight management may target children with overweight given prospects for prevention. Meanwhile, parents learn about weight-related genomics primarily through the media, and little is known about parental reactions to complex genomic and environmental causes underlying children's obesity risk. Methods: Three hundred twenty-four parents with overweight who have a child 3–13 years of age were recruited through Amazon Mechanical Turk. Parents were randomized to read an article highlighting one of three causes of obesity risk: genetics only, family environment only, gene–family environment interactions (G × FE), or read a control article. Results: Parents who perceived their child to be overweight exhibited increased risk perception and guilt over parents of lean children overall, but exhibited decreased worry in response to the G × FE message. Furthermore, parents of children with overweight who received the G × FE message did not exhibit heightened risk perception or guilt, reported that the message was less relevant, and that they paid less attention to it. Conclusions: Multifactorial causal information about children's obesity risk elicits unintended consequences among parents whose children are most at-risk for obesity in adulthood. As these messages are most accurate, it is crucial to investigate effective ways to communicate the holistic nature of obesity risk to parents.